A randomized, double-blind, positive-controlled, Phase-II clinical trial to evaluate efficacy and safety of Fuke Qianjin capsule in Pakistani patients with pelvic inflammatory disease - Shah, Muhammad Raza; Khan, Sehrosh Naz; Fatima, Samreen; Yao, Liangyuan; Yuan, Hongbo; Ullah, Shafi; Ainuddin, Jahanara; Zeng, Changqing; Zheng, Yiyang; Sahar, Najmus; Anwar, Shaista; Zhu, Meijun; et al. (Frontiers in Pharmacology, 2024)
Fuke Qianjin (FUKE) capsule is a Chinese herbal medicine used to treat various gynecological inflammatory diseases. To assess the safety and efficacy of FUKE capsule this phase 2, randomized, double blind, positive controlled clinical trial was conducted in mild to moderate symptomatic PID patients in Pakistan. Total 198 eligible female subjects with active PID were randomly assigned to test group (n=99) and control group (n=99). The test group subjects received metronidazole (METRO) 2 tablets and doxycycline hyclate (DOXY) simulants 1 tablet at a time; twice daily for 14 days and FUKE 2 capsules, thrice a day after meal for 28 days. Subjects in the control group received METRO 2 tablets and DOXY 1 tablet at a time; twice daily for 14 days and FUKE simulants 2 capsules, thrice a day after meal for 28 days. The primary efficacy outcome was the improvement in pelvic pain symptoms assessed through visual analogue scale. The secondary outcomes were the improvement in secondary efficacy symptoms like local physical signs, clinical assessment of leucorrhea and cervical secretions by lab examination; and improvement in maximum area of pelvic effusion assessed through gynaecological ultrasound. The safety outcomes were assessed through baseline characteristics and AEs/SAEs In the intention-to-treat analysis, the primary efficacy was 84.9% for test group and 71.6% for control group with a statistically significant difference (P=0.0370; 95% CI -0.2568 to -0.0088). The secondary clinical efficacy was 88.4% for test group and 82.7% for control group with no significant difference (P=0.2977; 95% CI -0.1632 to 0.0501). The improvement in local physical signs was 95.8% for test group and 76.9% for control group with no significant difference (P=0.0542; 95% CI -0.3697 to -0.0085). The inter-group comparison showed that the upper limit of 95% CI was less than 0.15 thus met the non-inferiority requirements of the test group to the control group. A total of 14 adverse events were observed in the trial and no serious adverse events occurred in the trial. Overall, results indicated that the FUKE capsule is non-inferior to the DOXY tablet in treating mild to moderate PID patients with comparable efficacy, safety and tolerability.